A meta-analytic review of the associations between dimensions of religious coping and psychological symptoms during the first wave of the COVID-19 pandemic - Cheng, Cecilia; Ying, Weijun (Frontiers in Psychiatry, 2023)
In the first wave of the COVID-19 pandemic, the unknown etiology and treatment of the highly transmissible coronavirus posed considerable threats to public mental health. Many people around the globe turned to religion as an attempt to mitigate their heightened psychological distress, but mixed findings have been obtained regarding the association between the use of religious coping and two psychological symptoms—anxiety and depressive symptoms—widely reported in the initial wave. The present meta-analysis was conducted to resolve the empirical inconsistency by synthesizing this body of studies and identifying both individual- and national-level factors that accounted for the inconsistent findings. Following PRISMA guidelines, the literature search and data screening procedures yielded 42 eligible studies, with 25,438 participants (58% females, average age = 36.50 years) from 24 countries spanning seven world regions. Overall, the results showed that only negative religious coping was positively associated with psychological symptoms (r = .2886, p < .0001). Although the associations of both general and positive religious coping with psychological symptoms were non-significant (rs = .0425 and −.0240, ps > .39), the moderation analysis revealed significant positive associations between positive religious coping and psychological symptoms in two demographic groups who experienced greater pandemic distress than their counterparts: younger participants and female participants. This meta-analysis provides a nuanced understanding of the complex nature of religious coping in the initial wave of the COVID-19 pandemic, when levels of public anxiety and stress were heightened. The exclusive use of religious coping may not be associated with low levels of psychological symptoms, implying the importance of supplementing the deployment of this strategy with an array of other strategies. Therapists of mental health interventions should show their clients how to make good use of positive religious coping together with other strategies, and how to avoid the use of negative religious coping, to handle their psychological problems.